Edukasi Dan Pelatihan Bank Sampah: Mewujudkan Lingkungan Berkelanjutan Dan Pemberdayaan Ekonomi Masyarakat Di Desa Sialang Panjang Kabupaten Indragiri Hilir Riau - Fahrina Yustiasari Liriwati; Muhammad Ilyas; Mulyadi Mulyadi; Abdul Syahid; Kafrawi Kafrawi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Empowering Early Childhood Communities through the Friendly Child House Program in Aenganyar Village, Giligenting Island, Sumenep. This program aims to provide special attention to early childhood and empower them through education, healthcare, social support, and parental empowerment. The program has a positive impact on improving the quality of life for children, developing skills, and promoting social values. Furthermore, it also builds strong relationships between children and the adults involved. The importance of empowering early childhood communities not only affects the present but also the future of children and society as a whole. Children are considered valuable assets to society and the nation, and ensuring they receive proper attention and support is a collective responsibility. The success of this program serves as an example for similar initiatives elsewhere and inspires further efforts in empowering early childhood.